1988
DOI: 10.1007/bf02181196
|View full text |Cite
|
Sign up to set email alerts
|

Side effects in excimer corneal surgery

Abstract: Thermal loading is a significant side effect during excimer laser surgery of the cornea. The maximal temperature rise, which is dependent on fluence and repetition rate of the radiation, amounts to 20 degrees C in excised corneas and 7.5 degrees C in the in situ cornea. The temperature decreases exponentially with increasing distance from the incision with a half-value distance of 610 +/- 100 micron. Exposure parameters are recommended to avoid temperature rises greater than 11 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
5

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 8 publications
3
50
0
5
Order By: Relevance
“…In addition, there is a randomised flying-spot ablation pattern, and controls the local repetition rates to minimise the thermal load of the treatment [23] (smooth ablation, no risk of thermal damage). Therefore, the ablated surface after aspheric wavefrontcustomised profiles is very smooth, so that there are some benefits in higher order aberrations.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there is a randomised flying-spot ablation pattern, and controls the local repetition rates to minimise the thermal load of the treatment [23] (smooth ablation, no risk of thermal damage). Therefore, the ablated surface after aspheric wavefrontcustomised profiles is very smooth, so that there are some benefits in higher order aberrations.…”
Section: Methodsmentioning
confidence: 99%
“…Korábbi tanulmányok megmutatták, hogy a PRK-kezelés közbeni maximális hőmérséklet-emelkedés korai léze-reknél akár 7,5 ˚C is lehet [13,14]. Pozitív korrelációt találtak az ablatio mélysége és a cornea felszíni hőmér-sékletének változása között [15].…”
Section: Megbeszélésunclassified
“…In addition, there are a randomized flying-spot ablation pattern, and controls for the local repetition rates to minimize the thermal load of the treatment 8 .…”
Section: Treatment Modalitymentioning
confidence: 99%
“…Though the rate of visual recovery may be slower in surface ablation thus lacking the LASIK 'wow' effect, studies have shown that LASEK is an effective modality for surgical correction of low to moderate myopia. [8][9][10] However, its utility for correction of high myopia is limited. [11][12][13] With introduction of thin and ultrathin flaps using femtosecond laser and newer microkeratomes such as the pendular microkeratome, the indications for the 2 surgical modalities are getting indistinct.…”
Section: Advances In Ophthalmology 230mentioning
confidence: 99%